Identity at Crossroad: An Assessment of Characters' Feelings and Observations in Sunil Bhatia's American Karma - Khanal, Baburam (Interdisciplinary Journal of Management and Social Sciences, 2021)
In recent years, scholars working in different array of humanities and other disciplines have taken intense interest in question concerning about identity. Students studying in postgraduate and undergraduate levels have devoted much of their research in identity politics of race, culture, gender, language and nationality. Hence, the term identity is not limited to one or two definitions, but it needs multiple explanations, plurality in interpretation and on top of that it demands heterogeneous elucidation, and through research.